CORRELATION BETWEEN THE KNOWLEDGE LEVEL OF ADOLESCENT WOMEN ABOUT REPRODUCTIVE HEALTH TOWARDS ATTITUDE IN EARLY MARRIAGE - Itdinah Rara Karima; Atika Atika; Rize Budi Amalia (Indonesian Midwifery and Health Sciences Journal, 2022)
Abstract